ANALISIS PERBANDINGAN KINERJA KEUANGAN ANTARA BANK MUAMALAT DAN BANK SYARIAH MANDIRI PERIODE 2015-2019 - Nurfauziah, Dhea; Trihantana, Rully; Kusumaningrum, Ria (SAHID BANKING JOURNAL, 2024)
This study aims to determine the financial performance of Bank Muamalat and Bank Syariah Mandiri and to find out whether there is a significant difference between the financial performance of Bank Muamalat and Bank Syariah Mandiri for the period 2015 to 2019. The subjects of this study were Bank Muamalat and Bank Syariah Independent. In this study using comparative and quantitative analysis methods and using secondary data, namely financial reports and annual reports published in 2015-2019. The results of this study are that Bank Muamalat and Bank Syariah Mandiri have good financial performance when viewed through the CAR ratio while viewed through NPF and FDR, Bank Muamalat and Bank Syariah Mandiri have good financial performance. With this research, it can be concluded that Bank Muamalat and Bank Syariah Mandiri show very good financial performance when viewed in terms of CAR ratio while when viewed in terms of NPF and FDR ratios Bank Muamalat and Bank Syariah Mandiri show good financial performance and there are significant differences on the financial performance of Bank Muamalat and Bank Syariah Mandiri where based on the ratio test (ROA, ROE, DGR, LGR, CAR) the performance of Bank Syariah Mandiri as a whole is better than the performance of Bank Muamalat.